1976
DOI: 10.1111/j.1471-0528.1976.tb00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Infections by Group B Β‐haemolytic Streptococci

Abstract: Since 1970 there has been an increase in isolations of Group B P-haemolytic streptococci from infants and mothers at the National Women's Hospital and the organism has become the major cause of fatal perinatal infection. Forty-three of 60 stillborn and liveborn infants with postmortem isolations of Croup B streptococci had pneumonia and of these a minority also had meningitis and/or septicaemia. Amnionitis was found in 15 of 20 placentae examined from these patients and an ascending infection from the maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 13 publications
(42 reference statements)
0
22
0
Order By: Relevance
“…Older infants, however, apparently may respond to and effectively localize infections, often to the meninges (41). In the United States, group B streptococci cause an estimated 3000 to 9000 cases per year of neonatal infection (1), including asymptomatic bacteremia, cellulitis, conjunctivitis, ethmoiditis, hypothalamic-pituitary dysfunction, impetigo, meningitis, omphalitis, osteomyelitis, otitis media, pleural and subdural empyema, pneumonia, respiratory distress, septicemia, and sup purative arthritis (12,18,20,21,32,34,37,41,49,64,71). Though less common than neonatal infections, reported adult infections include abor tion, abscesses, arthritis, empyema, endocarditis, meningitis, myocarditis, osteomyelitis, otitis media, peritonitis, pneumonia, postpartum infections, septicemia, and urinary tract infections (19,25,40,43,51,68-70, 87,93, 96).…”
Section: Clinical Significancementioning
confidence: 99%
“…Older infants, however, apparently may respond to and effectively localize infections, often to the meninges (41). In the United States, group B streptococci cause an estimated 3000 to 9000 cases per year of neonatal infection (1), including asymptomatic bacteremia, cellulitis, conjunctivitis, ethmoiditis, hypothalamic-pituitary dysfunction, impetigo, meningitis, omphalitis, osteomyelitis, otitis media, pleural and subdural empyema, pneumonia, respiratory distress, septicemia, and sup purative arthritis (12,18,20,21,32,34,37,41,49,64,71). Though less common than neonatal infections, reported adult infections include abor tion, abscesses, arthritis, empyema, endocarditis, meningitis, myocarditis, osteomyelitis, otitis media, peritonitis, pneumonia, postpartum infections, septicemia, and urinary tract infections (19,25,40,43,51,68-70, 87,93, 96).…”
Section: Clinical Significancementioning
confidence: 99%
“…An examination of the reference sections of excluded publications during full-text review resulted in the identification of two additional publications that met the criteria, for a final total of 17 publications. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] A third additional autopsy review identified through the bibliography search reported 13 stillbirths in which only GBS was isolated; 36 however, it was unclear whether the isolates were from placenta and/or fetal samples, and no details were given regarding study location or period. Attempts to obtain these details from the authors failed, and this study was therefore not included in the systematic review.…”
Section: Literature Searchmentioning
confidence: 99%
“…Five reports were identified from Sweden, 19,21,22,24,35 four from the USA, 23,29,30,34 two from Canada, 25,26 and one each from Zimbabwe, 33 Mozambique, 28 Lithuania, 31 Italy, 32 England, 27 and New Zealand. 20 A variety of different study designs were used, including three case-control studies, eight prospective cohort studies, and five retrospective reviews of autopsy files. Together, these studies captured a total of 99 cases of GBS-related stillbirth.…”
Section: Literature Searchmentioning
confidence: 99%
“…GBS sepsis can produce pulmonary hypertension, reduced cardiac output, hypoxemia, and V~Q mismatch in human neonates and neonatal animals (10)(11)(12). GBS-induced lung vascular injury also occurs as suggested by GBS invasion of lung capillary walls, intraalveolar hemorrhage and proteinrich pulmonary edema in human infants (13,14), and ultrastructural findings of lung capillary endothelial cell injury in both a piglet and nonhuman primate model of GBS sepsis (10,15). GBS infusion into piglets is delineated into an early ( < I h) and late phase (2 to 6 h) (11,12).…”
mentioning
confidence: 99%
“…GBS is a Gram-positive pathogen and the most common cause of neonatal sepsis (10)(11)(12)(13)(14). GBS sepsis can produce pulmonary hypertension, reduced cardiac output, hypoxemia, and V~Q mismatch in human neonates and neonatal animals (10)(11)(12).…”
mentioning
confidence: 99%